In vitro developmental competence of bovine demi-embryos generated by blastomere separation and blastocyst bisection - Ynsaurralde Rivolta, Amanda Eugenia; Gambini, Andrés; Alberio, Virgilia; Savy, Virginia; Ratner, Laura Daniela; Guberman, Alejandra; Vazquez Echegaray, Camila; Gismondi, Maria Ines; Curra, Anabella Paola; Bevacqua, Romina Jimena; Salamone, Daniel Felipe (Wiley, 2024)
The efficiency of bovine in vitro embryo production can be significantly improved by splitting embryos at different stages. However, the blastocyst quality of in vitro-produced demi-embryos remains unexplored. The objective of this research was to compare embryo developmental rates and quality of bovine demi-embryos produced by two different strategies: (a) embryo bisection (BSEC) and (b) 2-cell blastomere separation (BSEP). To determine demi-embryos quality, we evaluated total blastocyst cell number and proportion of SOX2+ cells. Additionally, the expression of SOX2, NANOG, OCT4, CDX2, IFNT, BAX and BCL genes and let-7a and miRNA-30c Micro RNAs was analysed. BSEP resulted in improved blastocyst development, higher ICM cells and a significantly higher expression of IFNΤ than demi-embryos produced by BSEC. Let-7a, which is associated with low pregnancy establishment was detected in BSEC, while miRNA-30c expression was observed in all treatments. In conclusion, BSEP of 2-cell embryos is more efficient to improve in vitro bovine embryo development and to produce good quality demi-embryos based on ICM cell number and the expression pattern of the genes explored compared to BSEC.